The Effect of Experiential Marketing on Perceived Service Value and Implications on Customer Loyalty - Tita Setiawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Experiential marketing has emerged as a powerful strategy to foster emotional and sensory engagement between consumers and brands. This study investigates the direct impact of experiential marketing on customer loyalty and examines the mediating role of perceived service value in the context of restaurants and cafés in Bandung, Indonesia, a city known for its rapidly growing food and beverage industry. Drawing on data collected from 200 valid questionnaires, this research employs a quantitative explanatory design and utilizes Structural Equation Modeling (SEM) with AMOS software to analyze the relationships among variables. The results indicate that experiential marketing significantly enhances both perceived service value and customer loyalty. Moreover, perceived service value is found to mediate the relationship between experiential marketing and customer loyalty partially. These findings highlight the importance of designing immersive and emotionally engaging experiences not only to satisfy but also to retain customers in the competitive hospitality sector. By integrating experiential marketing strategies that elevate perceived value, restaurant and café businesses can strengthen long-term customer relationships. This study contributes to both academic literature and managerial practice by offering empirical evidence on the mechanisms through which experiential marketing influences loyalty in an emerging market setting.